Investigation of user behavior and assessment of typical operation mode for different types of firewood room heating appliances in Austria. (August 2016) - Reichert, G.; Schmidl, C.; Haslinger, W.; Schwabl, M.; Moser, W.; Aigenbauer, S.; Wöhler, M.; Hochenauer, C.
Abstract: Firewood heaters like firewood roomheaters, tiled stoves and residential biomass cookers are commonly used for supplying the residences with renewable heat. However, these kinds of appliances were identified as responsible for relevant amounts of gaseous CO and OGC as well as particulate emissions causing negative health effects. Beside technological reasons, the operating conditions and the user behavior are essential reasons for increased emissions, especially in real life operation. Therefore, this study aimed at an investigation and assessment of typical real life user behavior by a survey. Based on the findings effective and customer friendly technological and non-technological optimization approaches for a better and more environmental friendly real life performance were defined. The results of the study showed principally similar user behavior of all considered types of appliances regarding most relevant operation characteristics, i.e. kind, properties and amount of used fuels, ignition procedure and air valve settings. Most effective non-technological optimization approaches were found for an enhancement of external training arrangements and the development of user friendly manuals that aimed mainly at an improvement of the ignition procedure from bottom–up to top–down ignition method. The use of devices with an automatically controlled combustion air supply was identified as promising technological measure. Highlights: Assessment of real life operation of firewood room heating appliances. Evaluation of typical real life operation of firewood room heating appliances. Basis for technological and non-technological customer-tailored development. Basis for development of advanced test methods focusing on real life conditions.